Macroporous alginate foams crosslinked with strontium for bone tissue engineering. (15th December 2018) - Catanzano, Ovidio; Soriente, Alessandra; La Gatta, Annalisa; Cammarota, Marcella; Ricci, Giulia; Fasolino, Ines; Schiraldi, Chiara; Ambrosio, Luigi; Malinconico, Mario; Laurienzo, Paola; Raucci, Maria Grazia; Gomez d'Ayala, Giovanna
Graphical abstract: Highlights: Combination of internal gelation technique with gas foaming produces macroporous alginate foams. Alginate was cross-linked by a mixture of Sr and Ca ions. Increase of Sr 2+ concentration leads to higher stability in physiological conditions. High Sr 2+ concentration promotes osteogenic marker expression. All foams reduce ROS and basal nitric monoxide production. Abstract: Nowadays, the need of novel strategies to repair and regenerate bone defects in the field of biomedical applications has increased. Novel approaches include the design of natural bioactive scaffolds mimicking bone tissue. These bioactive scaffolds have to possess biophysical properties suitable to address biological response towards newly bone tissue formation. In particular, scaffold porosity and pore size play a pivotal role in cell migration, adhesion and proliferation, thus increasing cell-material surface interaction and osteogenic signals transmission. Here we propose the development of macroporous alginate foams (MAFs) with porous and well interconnected structure, useful to enhance growth and osteogenic differentiation of human Mesenchymal Stem Cells (hMSCs). Moreover, in this study we report a new method for MAFs fabrication based on the combination of internal gelation technique with gas foaming. Strontium was employed in combination with calcium as cross-linking agent for the alginate chains and as enhancer of the osteogenic differentiation. The influence of strontium ions on the gelation kinetics, physical properties and degradation in physiological medium of MAFs was investigated. Our results suggest that the combination of internal gelation technique with gas foaming followed by freeze-drying is an easy and straightforward procedure to prepare alginate foams with high porosity and interconnectivity, able to support cell infiltration. Finally, biological assays showed how scaffolds with high strontium content are able to support cell growth and differentiation in long times by promoting osteogenic marker expression.